The Post-Intensive Care Syndrome in Children - Ekim, Ayfer (Taylor & Francis Inc, 2020)
Improvements in devices and techniques used to provide life support for patients at intensive care units have reduced patient mortality. Increases in the number of survivors from a critical illness have brought long-term complications experienced during the post-intensive care period into question. The term post-intensive care syndrome (PICS) is defined as a new and deteriorating disorder in the cognitive, mental, and physical health status experienced by the survivor after intensive care unit discharge that might continue for months or even years. Opioid and sedation exposure, the severity of illnesses and injuries, dense life support interventions, length of stay in the intensive care unit, and social isolation constitute risk factors for PICS in children. These factors cause the child to experience deterioration in physical, cognitive, and psychological health domains. Such deteriorations occur on various levels and have negative effects on quality of life. The purpose of this article is to raise awareness and help pediatric nurses to develop an understanding of the condition. Increasing awareness by pediatric nurses about the magnitude and effects of complications after discharge from the intensive care unit will be the first step to protect survivors from new problems, to provide assistance for ongoing problems, and to develop follow-up strategies. PICS-related morbidities affect the majority of children discharged from PICUs. We need to understand the scope of those morbidities and develop efficient nursing interventions accordingly. It is time to expand our goal for critical and noncritical care from life-saving into improvement of functional health status and quality of life.
Keywords: Children; Critical İllness; Pediatric İntensive Care; Survivor; Quality-Of-Life; Survivors; Unit; Discharge; Admission; Recovery; Illness